First Nation Peoples' nutrition and exercise group programmes: transforming success through the lifeworld. Issue 1 (1st January 2021) - Urquhart, Lisa; Fisher, Karin; Duncanson, Kerith; Roberts, Karen; Munro, Simon; Gibbs, Clinton; Brown, Leanne
ABSTRACT: Purpose: Previous literature has applied system-focused structures to understand the success of First Nations Peoples' nutrition and exercise group programmes. Existing system-focused measures have included biomedical outcomes, access and service utilization. By broadening the focus of programme success beyond the system, we can evaluate programmes from a First Nations Peoples' lifeworld perspective. Critical hermeneutics and yarning using a lens of Habermas' Theory of Communicative Action to the literature has the potential to transform understandings of "success" in First Nations Peoples' nutrition and exercise group programmes. Methods: In this literature interpretation, we explored the critical success factors from a lifeworld perspective, giving scope to go beyond a system perspective to include a cultural, social or personal perspective. Results: Our yarning led us to understand that there is a communicative relationship between explicit system structures and implicit lifeworld concepts that are critical success factors for First Nations nutrition and exercise group programmes. We have developed a set of reflective questions to guide others in considering a lifeworld perspective. Conclusions: Our findings represent a shift away from success measured by the dominant power structure to respect the lifeworld culture, knowledges and values of First Nations Peoples towards shared understanding and mutual decision-making.